DETERMINAN PENGGELAPAN PAJAK OLEH WAJIB PAJAK ORANG PRIBADI - Putri, Kavita Istitania Tri Buana; Hidayatulloh, Amir (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
The aim of this research is to analyze the determinants of tax evasion committed by individual taxpayers. The population of this research is individual taxpayers in Sleman Regency. Meanwhile, the sample for this research is individual taxpayers in Sleman Regency who have a NPWP. The sampling technique used purposive sampling, the criteria were (1) Muslim, and (2) not an employee. Data was collected by distributing questionnaires directly to respondents who met the criteria. The number of respondents to this research was 35 respondents. The data analysis technique for this research uses multiple linear regression analysis with the help of SPSS. This research found that tax evasion was not influenced by money ethics, materialism, intrinsic religiosity, extrinsic religiosity, and gender.